2004
DOI: 10.1128/jcm.42.6.2465-2469.2004
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Evidence of Infections withBabesia gibsoniParasites in Japan and Evaluation of the Diagnostic Potential of a Loop-Mediated Isothermal Amplification Method

Abstract: Detection and analysis of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
51
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 105 publications
(57 citation statements)
references
References 16 publications
5
51
0
1
Order By: Relevance
“…All positive serum samples from domestic dogs both from Japan and China were IFAT-positive (data not shown). The present data of prevalence of canine B. gibsoni infection in western Japan is within the range reported previously [10,11,18]. In addition, to our knowledge, this is the first report describing a survey on canine piroplasmosis in Nanjing, China.…”
Section: Discussionsupporting
confidence: 63%
“…All positive serum samples from domestic dogs both from Japan and China were IFAT-positive (data not shown). The present data of prevalence of canine B. gibsoni infection in western Japan is within the range reported previously [10,11,18]. In addition, to our knowledge, this is the first report describing a survey on canine piroplasmosis in Nanjing, China.…”
Section: Discussionsupporting
confidence: 63%
“…Haemaphysalis species has an especially wide geographical distribution, including Aomori Prefecture [23]; therefore, the vector ticks might have contributed to the spread of B. gibsoni infection among Tosa dogs, but dogs with acute B. gibsoni infection were not recognized in dogs of any other breed. Furthermore, natural infection with this pathogen, as identified by PCR assays, has been found only in dogs of the Tosa breed, and has not been identified in tests of 872 dogs of other breeds in dogs of any other breeds in Aomori Prefecture [11]. It has been reported in 2003, that B. gibsoni parasite was not detected in ticks from eastern Japan, including Aomori Prefecture, in an epidemiological survey [12].…”
Section: Discussionmentioning
confidence: 99%
“…This technique has been proven to be an accurate, rapid and simple method, which amplifies the target nucleic acid under isothermal conditions (Notomi et al, 2000). Recently, wide applicability of LAMP in the detection of parasitic protozoa such as Babesia, Plasmodium, Leishmania and Trypanosoma in clinical samples has been demonstrated (Ikadai et al, 2004;Poon et al, 2006;Njiru et al, 2008;Takagi et al, 2009;Thekisoe et al, 2007;Laohasinnarong et al, 2011). Studies have also shown the application of LAMP to survey vectors of infectious diseases (Aonuma et al, 2009;Thekisoe et al, 2010;Nakao et al, 2010); however, these studies used purified DNA as a template for the LAMP assays.…”
Section: Introductionmentioning
confidence: 99%